The proGnostic role of caRdiac rehAbilitation in patients with left ventriCular anEurysm formation after anterior myocardial infarction (the GRACE study): Study rationale and design of a prospective randomized controlled trial - Zhang, Peng; Ge, Xiaofeng; Li, Zhaokai; Nie, Meiling; Yu, Jing; Ou, Weimei; Wu, Kaimin; Li, Jiahua; Wang, Lin; Ni, Wei; Shi, Zaixing; Song, Juan; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background Cardiac rehabilitation (CR) is an essential intervention after acute myocardial infarction (MI). However, it is still unclear whether patients with left ventricular aneurysm (LVA) formation after anterior MI would benefit from CR programs. This clinical trial is designed to assess the role of CR in patients with LVA formation after anterior MI. Trial design The GRACE study is a single-center, single-blind, prospective, randomized controlled clinical trial in China. 100 subjects aged 18-75 years with LVA formation after anterior MI will be recruited and randomized 1:1 to the CR or control group. Both groups will receive standard drug treatment and routine health education according to the guidelines. Participants in the CR group will additionally receive tailored CR programs delivered over a period of 36 sessions. These participants will then be followed up for 1-year. The primary outcome is peak oxygen uptake measured by cardiopulmonary exercise testing after CR programs. The secondary outcomes are cardiac function and EuroQol 5-Dimension-3 Level index scores after CR program and 1-year and major adverse cardiac cerebrovascular events, a composite of cardiovascular mortality, non-fatal MI, non-fatal stroke, malignant arrhythmia or hospitalization for heart failure during the follow-up period. Conclusions This single-center, single-blind, prospective, randomized controlled clinical trial will determine whether CR improves physical capacity and clinical outcomes in patients with LVA formation after anterior MI. Trial registration Chinese Clinical Trial Registry ChiCTR2200058852. Registered on 18 April 2022.